Fractional Quantum Hall States in Bilayer Graphene Probed by Transconductance Fluctuations - Kim, Youngwook; Lee, Dong Su; Jung, Suyong; Skakalova, Viera; Taniguchi, T.; Watanabe, K.; Kim, Jun Sung; Smet, Jurgen H. (AMER CHEMICAL SOC, 2015)
We have investigated fractional quantum Hall (QH) states in Bernal-stacked bilayer graphene using trans-conductance fluctuation measurements. A variety of odd-denominator fractional QH states with nu(QH) --> nu(QH) + 2 symmetry, as previously reported, are observed. However, surprising is that also particle-hole symmetric states are clearly resolved in the same measurement set. We attribute their emergence to the reversal of orbital states in the octet level scheme induced by a strong local charge imbalance, which can be captured by the transconductance fluctuations. Also the even-denominator fractional QH state at filling -1/2 is observed. However, contrary to a previous study on a suspended graphene layer [Ki et al. Nano Lett. 2014, 14, 2135], the particle-hole symmetric state at filling 1/2 is detected as well. These observations suggest that the stability of both odd and even denominator fractional QH states is very sensitive to local transverse electric fields in bilayer graphene.
Keywords: BROKEN-SYMMETRY STATES; QUASI-PARTICLES; BERRYS PHASE; LOCALIZATION; CHARGE; EXCITATIONS